Napier: Miraculous fodder grass for the dry hot regions of Western Rajasthan - Singh, Ishwar; Singh, S K; Kumar, Mahendra; Kumari, Shilpa; Singh, Garbar (Indian Farming, 2021)
The farmers of Western Rajasthan faces shortage of green fodder during extreme summer season. Productivity of Lucerne and other green grasses reduced during summer and repeated irrigations are required to take sufficient green fodder from these crops. Napier grass as green fodder can be a good alternate under these circumstances. With this objective, it was introduced at 20 farmer’s sites in 2 successive years during 2018-19 and 19-20. Results were very encouraging. Napier grown under drip irrigation system saved good quantity of water and provided huge quantity of green fodder for the cattles reared at every farm in the area. This technology has a horizontal expansion of more than 200 farmers of nearby areas.